Systolic Nanofabrication of Super-Resolved Photonics and Biomimetics - Konstantina Papachristopoulou; Nikolaos A. Vainos (Nanomaterials, 2020)
Systolic nanofabrication is demonstrated via conformal downsizing of three-dimensional micropatterned monolithic master-casts made of extremely nanoporous aerogel and xerogel materials. The porous solid skeleton collapses by thermal treatment, generating miniaturized replicas, which preserve the original stereometric forms and incorporate minified nanoscale patterns. Paradigmatic holographic and biomimetic nanoarchitectures are conformally downsized by ~4×, yielding subwavelength surface features of less than ~150 nm. The operations demonstrate the super-resolution capabilities of this alternative concept and its potential evolution to an innovative nanotechnology of the future.